Development of UKBM Based on EPUB (Human Digestive System) - Novela Memiasih; Murni Sapta Sari; Triastono Imam Prasetyo; I Wayan Sumberartha (Universitas Negeri Malang, 2021)
In this globalization era, information is very easy to obtain, therefore critical thinking skills are important for students to have because they can train students to filter the information obtained to solve a problem. The purpose of this research is to produce a product in the form of UKBM based on ePUB on digestive system topic to improve critical thinking skills and cognitive learning outcomes of students who have been tested for validity, practicality and effectiveness. The development model used in this study is the ADDIE development model. The study was conducted at SMA Negeri 5 Malang with the research sample being students of class XI. Research data in the form of the results of the validation of media experts, topic experts, assessment experts, field practitioners, student responses, pretest and posttest results of students. The results showed that the average percentage of validated ratings of media experts, topic experts, assessment experts, field practitioners were 96.74 percent, 100 percent, 100 percent, and 94.23 percent, all of which were in the very valid category. The practicality test value is 92.53 percent which means it is very practical, the value of the effectiveness test is 0.8 which means it is classified as very effective, the results of students critical thinking skills are 82.16 which means it is classified as very critical, and the cognitive learning outcomes of students 93.42 which means it is classified as high. Based on the results of the study it can be concluded that the development of UKBM based on ePUB can improve critical thinking skills and students cognitive learning outcomes.